Building “in-common” situations through inoperative technologies (Res Publica. Revista de Historia de las Ideas Políticas, 2014)
the following text is an approach to the possibilities offered by the development of technology in the field of communication for the construction of communities of interaction among equals. With the help of the french philosopher alain Badiou’s philosophical theory on the “inoperative community” we intend to show that a situation of communication among equals requires the anonymity of its members, its infinite openness and its ubiquity. taking these premises as a starting point we shall analyse (uSa)/analyse (uK) the so-called mobile networks of communication between peers or P2P (MaNEt). our aim is to propose the anonymous, open and ubiqui - tous infrastructure underlying these communication networks as a necessary operator for the construction of communicative situations based on egalitarian premises.